Pengaruh Struktur Kepemilikan terhadap Tax Avoidance dengan Profitabilitas sebagai Variabel Moderasi - Sulistiyani, Dwi Eni; Rizkyana, Fitrarena Widhi (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study empirically examines the effects of ownership structure, including managerial, institutional, and public ownership, on tax avoidance practices, using profitability as a moderating variable. The population in this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX), from which a sample was selected using purposive sampling. A total of 330 observations were collected from 110 manufacturing companies for the period 2022–2024. The variables were tested using multiple linear regression in EViews 12. This study expands on previous research by using profitability as a moderating variable that can influence the relationship between ownership structure and tax avoidance. The results show that institutional ownership has a negative and significant effect on tax avoidance practices. An increase in institutional share ownership can reduce tax avoidance practices. Meanwhile, managerial and public ownership do not affect tax avoidance practices. In the moderation test, profitability strengthened the effect of managerial and institutional ownership on tax avoidance. Still, it did not moderate the impact between public ownership and tax avoidance.